In vivo evaluation of 3-dimensional PLGA/ Atelocollagen/ Fibrin scaffolds for intervertebral disc (IVD) regeneration - Mohamad, Mohd Yusof; Mohamed Amin, Muhammad Azri Ifwat; Zulkifly, Ahmad Hafiz; Sha'ban, Munirah (2016)
Poly (lactic-co-glycolic acid) (PLGA) is a widely used synthetic biomaterial in tissue engineering. Incorporation of natural atelocollagen and fibrin may provide PLGA a better surface property for cellular adhesion and proliferation. This paper aims to evaluate PLGA/Atelocollagen/Fibrin hybrid scaffolds seeded with IVD’s annulus fibrosus (AF) cells after in vivo implantation. Porous 3D PLGA were fabricated via solvent-casting and salt-leaching technique. PLGA was crosslinked with atelocollagen (PA). Fibrin was pipetted onto PLGA (PF) and PA (PAF) scaffolds. Rabbits’ AF cells were seeded onto each scaffold groups i.e. PLGA only, PA, PF and PAF. The “cells-scaffolds” constructs were cultured for three-weeks and implanted subcutaneously in athymic nude mice for four-week. All constructs were evaluated for gross morphology, histology, immunohistochemistry (IHC) against collagen I and II with PLGA construct as control group. Sulphated glycosaminoglycan (sGAG) and DNA contents were compared to that of monolayer AF culture. All groups exhibited significant reduction in size but showed increment in weight. Histology analysis indicated high cellular density, supported by high DNA content in all groups. The IHC showed presence of collagen I and II. The PAF showed a significantly higher sGAG content than the other groups. Degradation of PLGA did not hinder tissue formation. Atelocollagen and fibrin may contribute to a higher cellular proliferation and extracellular matrix production in PLGA. Further evaluation using gene expression shall be performed to study the intrinsic properties and possible mechanisms involved. PLGA/Atelocollagen/Fibrin hybrid scaffolds may become potential candidate for tissue engineering application.